(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Newest advancements in micro-electro-mechanical-system (MEMS) and wirelesscommunication technology unlock the way for the development in applications of wireless sensornetworks (WSNs). Wireless sensor network is comprised of vast number of minute and cheap devicesknown as sensor nodes. The sensor nodes work together by a lot of wireless strategies and thesestrategies are administered by routing protocols. Performance of sensor networks mainly depends onthe routing protocols which are request based. Based on structure of network routing protocols in WSNcan be largely classified into three categories flat routing, hierarchical or cluster based routing, andlocation based routing. Due to sure advantages, clustering is gratifying as a lively stem in routingtechnology. In this paper, authors have been reported a complete survey on cluster based routingprotocols in wireless sensor networks. We sketch the merits and limitations of the clustering schemesin WSNs, and propose a classification of cluster based routing methods. Lastly, we summarize and bringto a close the paper with some future directions.